OVERVIEW OF DIAGNOSIS AND TREATMENT OF FEMALE HYPOACTIVE SEXUAL DESIRE DISORDER (Vietnam Journal of Community Medicine, 2022)
Background: Female sexual dysfunction has only been studied from a modern perspectivefor more than six decades and is evolving rapidly [1]. “Female hypoactive sexual desiredisorder” was first reported in the DSM-III 41 years ago [2], however, so far the understandingof physiology, pathogenesis, diagnosis, and treatment is still limited.Aim: To develop an overview of the diagnosis, approach, and treatment of female hypoactivesexual desire disorder.Methods: Synthesis and analysis of studies on female hypoactive sexual desire disorderand the latest guidelines on diagnosis and treatment of the International Society for theStudy of Women’s Sexual Health, the International Consultation on Sexual Medicine, TheInternational Society for Sexual Medicine.Results: Complete an update on the diagnosis and treatment of female hypoactive sexualdesire disorder.Conclusions: The Decreased Sexual Desire Screener is essential to screen for femalehypoactive sexual desire disorder. Asking about the disease, and exploiting psychological,physiological, relationship, and social factors are extremely important for diagnosis andtreatment orientation. The treatment of female hypoactive sexual desire disorder may engageboth psychosocial and biological strategies. This review aims is to develop an overview ofthe diagnosis, approach, and treatment of female hypoactive sexual desire disorder.
Keywords: Female sexual dysfunction, female hypoactive sexual desire disorder.